Sosialisasi Bahaya Kadar Logam Berat Timbal Pada Ikan Dari Kolong Bekas Tambang Di Desa Sungaiselan Atas, Bangka Tengah - yussa yussa; Putri Putri; Ardiansyah Kurniawan (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Tempalak fish obtained from the former lead has accumulated lead heavy metal with an average of 1.33 mg/Kg The value exceeds the safety threshold of 0.3 mg/Kg. Research results that show the potential danger of heavy metals in fish obtained from kolong if consumed by humans need to be socialized to stakeholders related to the community. This information is expected to be a warning and disseminated to the public to be vigilant. The socialization to Sungaiselan Atas Village will be held on November 10, 2022. The location of the service is at the Sungaiselan Atas Village office in Sungai Selan District, Bangka Tengah Regency. The implementation of socialization uses a discussion approach with village officials to provide information about the heavy metal content of fish caught from the kolong. The results of this initial research were received by the Sungai Selan Atas village to be the subject of their discussion with the community.